2023
DOI: 10.1111/ijfs.16466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flaxseed lignan on the dynamics of Lactiplantibacillus plantarum and starter cultures in fermented milk

Abstract: SummaryThe lignan from milled defatted flaxseed powder (DFP) and defatted hull powder (DHP) was extracted using direct alkaline hydrolysis and the quantity of lignan in the extract was estimated to be in the range of 11.74–14.30 mg g−1 flaxseed on a dry matter basis. Qualitative and quantitative analysis of different strains of Lactiplantibacillus plantarum (A1, Lp9, A5) along with yogurt mix culture (NCDC 146), Streptococcus salivarius ssp. thermophilus (NCDC 74) and Lactobacillus delbrueckii ssp. bulgaricus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Our previous research describes the extraction of SDG by direct alkaline hydrolysis coupled with magnetic stirring, microwave, and ultrasound; HPLC and FTIR estimation of SDG from defatted whole flaxseed and hull; and their effect on starter and probiotic culture [19]. Briefly, SDG was extracted from milled defatted flaxseed flour using direct alkaline hydrolysis coupled with magnetic stirring.…”
Section: Development Of Flaxseed Lignan-enriched Set Dahimentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research describes the extraction of SDG by direct alkaline hydrolysis coupled with magnetic stirring, microwave, and ultrasound; HPLC and FTIR estimation of SDG from defatted whole flaxseed and hull; and their effect on starter and probiotic culture [19]. Briefly, SDG was extracted from milled defatted flaxseed flour using direct alkaline hydrolysis coupled with magnetic stirring.…”
Section: Development Of Flaxseed Lignan-enriched Set Dahimentioning
confidence: 99%
“…The total viable count and probiotic count of SDG-enriched dahi were not significantly different from those of the control (p > 0.05). A thorough investigation of the effects of SDG on Lactiplantibacillus plantarum and starter cultures found that flaxseed lignan did not impact their fermentation dynamics [19].…”
Section: Physico-chemical Textural Sensory and Microbiological Attrib...mentioning
confidence: 99%